SELECTION OF DROUGHT TOLERANT WHEAT GENOTYPES BASED ON MEAN PERFORMANCE AND BIPLOT ANALYSIS - AFZAL, M; KHALID, MN; IMTIAZ, M; NASIR, B; SHAH, SAH; NAWAZ, M; NAYAB, SF; MALIK, SN; MAJEED, T; MAQBOOL, R (Biological and Clinical Sciences Research Journal, 2023)
The effect of water deficiency was assessed on the productivity of different wheat genotypes viz., Pasban-90, T-11, C-271, LU-26, Seher-06, AARI-11, Maxi-Pak 1965, Ujala-16, Chakwal-50 and Anaj-17 using triplicate Randomized Complete Block Design under two environmental conditions i.e., normal and drought. The trials were planted in the experimental field area of University of Agriculture Faisalabad, Pakistan. Four irrigations were applied to normal condition trial while drought one was only dependent on natural precipitation. All characters showed highly significant results for irrigation except for spike length and grains per spike. Mean values were computed from raw data and represented by graphs in which values for each trait was compared separately for both drought and normal condition of irrigation. Under drought condition of irrigation, maximum grain yield mean value was of Ujala-16 while minimum grain yield value was of Seher-06. Biplots were plotted from mean values of each trait for both conditions of irrigation separately to analyze performance of each genotype individually. The genotype which performed best under both condition for grain yield per plant was Anaj-17. The most susceptible genotype to drought was Seher-06. Under drought condition, the genotypes which performed best were Ujala-16, C-271 and Chakwal-50. The best performing genotype under normal condition of irrigation was C-271 for grain yield per plant. The results obtained could be proved helpful in selecting best wheat genotypes for improving breeding program to increase average production of economically important crop.